2014
DOI: 10.3928/15394492-20140211-01
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Longitudinal Study Testing Relationships between Meaningful Activities, Basic Psychological Needs Fulfillment, and Meaning in Life

Abstract: Meaningful activity and meaning in life 2 AbstractThe present study employed a prospective longitudinal design to determine if change in meaningful activity over an 11-month period could help to explain change in meaning in life in a sample of 174 undergraduate and graduate students. The Engagement in Meaningful Activities Survey, Basic Psychological Needs Scales (i.e., autonomy, competence, and relatedness), and the Meaning in Life Questionnaire were used as indicators of the constructs of meaningful activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 43 publications
0
32
1
Order By: Relevance
“…Our study found engagement in meaningful activity is positively related to meaning in life in a student veteran sample, adding to models and research by King (2004) andEakman (2014). Eakman (2014) found that engagement in meaningful activity predicts meaning in life, a sentiment echoed by Weinstein et al (2013) and King (2004), indicating that engaging in activity could be an important source of meaning-making (Eakman, 2014).…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Our study found engagement in meaningful activity is positively related to meaning in life in a student veteran sample, adding to models and research by King (2004) andEakman (2014). Eakman (2014) found that engagement in meaningful activity predicts meaning in life, a sentiment echoed by Weinstein et al (2013) and King (2004), indicating that engaging in activity could be an important source of meaning-making (Eakman, 2014).…”
Section: Discussionmentioning
confidence: 67%
“…Eakman (2014) found that engagement in meaningful activity predicts meaning in life, a sentiment echoed by Weinstein et al (2013) and King (2004), indicating that engaging in activity could be an important source of meaning-making (Eakman, 2014). Although our observed difference in means was only approaching significance, exploration of meaningful activity involvement in veterans represents a potential area for future occupational therapy research because of its relevance to the practice of occupational therapy and the relationship of PTSD and depression to activity avoidance (APA, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…547] while engagement in occupation helps bring meaning and coherence into our lives (e.g., [65,66]. Eakman [6] commented that the subjective quality of experience or meaning associated with engagement in activity may be a key mechanism through which day-to-day action influences personal well-being, such as meaning in life [49,68]. Moreover, occupational dysfunction has been found related to both social participation and to decline in health-related quality of life [69].…”
Section: Activities and Participation: Bishop Robert South Wrote Thatmentioning
confidence: 99%
“…However, throughout the life cycle humans need to modify their behavior to adapt to daily activities [6]. Studies that associate the concept of homeostasis to human behavior focus mainly on socio-emotional and psychological behavioural adaptations or adjustments in response to stressful events, e.g., [3,7].…”
mentioning
confidence: 99%